Is Collective Titling Enough to Protect Forests? Evidence from Afro-descendant Communities in the Colombian Pacific Region (2019)
During the mid-1990s, one of the most ambitious land reforms in recent decades took place in Colombia. The reform recognized collective land rights of 5 million hectares by Afro-Colombian groups, with the dual goals of improving livelihoods and preserving valuable ecosystems. We estimate the impact of this collective land titling program on forest cover using panel data and a difference-in-difference empirical strategy. We find that overall, collective titling significantly reduces deforestation rates, but the effect varies substantially by sub-region. We observe that the larger effects are in Nariño and Valle del Cauca especially in places with higher deforestation threat, closer to the forest frontier, to roads, and to navigable rivers, as well as in places without illegal crops. Our qualitative analysis suggest that this might be the result of communities being able to expel private companies from their lands which is more challenging with actors promoting illegal crops. We conclude that under the adequate conditions, titling can lead to forest conservation.